Microbially Induced Calcium Carbonate Precipitation as Bio-Mimetics Material in Applications of Slashing Carbon Emission and Carbon Sequestration: A Review - Ramadhani, Ramadhani; Said, Ahmad (Cipasung Techno Pesantren: Jurnal Ilmiah, 2024)
Concrete production contributes radically to global carbon dioxide emissions. Microbially induced calcium carbonate precipitation (MICP) is an evolving technology that allows calcium carbonate to be precipitated on concrete through microbial metabolic activity. This review paper aims to present an overview of contemporary findings on the solicitation of MICP for advancing the properties of concrete, reducing carbon emissions from cement production, and elevating carbon sequestration. The results of previous studies have expounded that MICP treatment can enhance the compressive strength, stiffness, and durability of concrete. More importantly, MICP technology propounds the potential to moderately supersede cement content in concrete, thereby lowering carbon emissions from cement production. The microbial precipitated calcium carbonate may also accelerate the sequestration of carbon dioxide. While more research is still needed, MICP shows capacity as a sustainable technique for developing low-carbon concrete materials.